2015
DOI: 10.3390/molecules200917244
|View full text |Cite
|
Sign up to set email alerts
|

Editorial of Special Issue Ruthenium Complex: The Expanding Chemistry of the Ruthenium Complexes

Abstract: Recent trends in Ru complex chemistry are surveyed with emphasis on the development of anticancer drugs and applications in catalysis, polymers, materials science and nanotechnology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 325 publications
(317 reference statements)
0
45
0
5
Order By: Relevance
“…38 Many Ru(III) compounds contain exchangeable ligands and require activation by the tumor microenvironment. 39 The antitumor properties of the Ru(III) complexes occur when they are reduced to their corresponding Ru(II) counterparts in vivo . Under biological circumstances of low oxygen concentration, acidic pH and high levels of glutathione, the Ru(II/III)redox potential can be altered, and thus, Ru(III) complexes can be readily reduced to Ru(II) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…38 Many Ru(III) compounds contain exchangeable ligands and require activation by the tumor microenvironment. 39 The antitumor properties of the Ru(III) complexes occur when they are reduced to their corresponding Ru(II) counterparts in vivo . Under biological circumstances of low oxygen concentration, acidic pH and high levels of glutathione, the Ru(II/III)redox potential can be altered, and thus, Ru(III) complexes can be readily reduced to Ru(II) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a number of ruthenium complexes, which exhibit interesting physico-chemical and biochemical properties, associated with low toxicity profiles, have been recently identified and intensively studied910. Many ruthenium complexes have in fact shown selective bioactivity, as well as the ability to overcome the resistance encountered with platinum-based drugs, ranking them as strong antitumoral candidates in a rational drug discovery approach11. Among these, ruthenium(III) compounds behave as valid prodrugs with somehow limited side-effects11, being likely activated to the more reactive and cytotoxic ruthenium(II) derivatives within the reducing microenvironment of solid tumours12.…”
mentioning
confidence: 99%
“…Many ruthenium complexes have in fact shown selective bioactivity, as well as the ability to overcome the resistance encountered with platinum-based drugs, ranking them as strong antitumoral candidates in a rational drug discovery approach11. Among these, ruthenium(III) compounds behave as valid prodrugs with somehow limited side-effects11, being likely activated to the more reactive and cytotoxic ruthenium(II) derivatives within the reducing microenvironment of solid tumours12. Along with ligands release and/or substitution - which occurs rapidly under physiological conditions in vitro and in vivo - the biological reduction of ruthenium(III) complexes is a possible process, especially in high proliferating cells, thereby promoting a unique activation process of this kind of metal-based drug in tumour tissues12.…”
mentioning
confidence: 99%
“…14,15 As previously discussed, the unique properties of Ru-based complexes, including their high ability to bind nucleic acids and proteins and undergo ligand exchange reaction, the prevalence of the two main oxidation states, Ru(II) and Ru(III), as well as the iron-mimicking property when bound to biological molecules have made them potential drug candidates for various medical applications. 16 In addition, these complexes have reduced toxicity and can be well tolerated in vivo. 17 Studies have also shown that most Ru complexes have low systemic toxicity, exhibit slow ligand exchange rates similar to that of platinum compounds, and can accumulate in cancer cells more effectively than platinum.…”
mentioning
confidence: 99%
“…18 As listed in Table 2, although a large number of Ru complexes have shown great promise as potential antitumor agents, only three complexes, NAMI-A, KP1019, and NKP1339 (Table 3), have entered clinical trials. 16,19,20 Clinically, all the three complexes exhibited promising anticancer activities with minimal side effects; an ideal property of a good anticancer drug (Table 3). In addition, these complexes have octahedral coordination geometry with respect to the Ru(III) metal center; however, they exhibit different biological activities despite their structural and chemical similarities.…”
mentioning
confidence: 99%